Bioisosteric modification of known fucosidase inhibitors to discover a novel inhibitor of α-l-fucosidase. Issue 6 (13th January 2017) - Bathula, Chandramohan; Ghosh, Shreemoyee; Hati, Santanu; Tripathy, Sayantan; Singh, Shailja; Chakrabarti, Saikat; Sen, Subhabrata
Abstract : Hydantoin, thiohydantoin and pyridone analogs as α-l -fucosidase inhibitors through bioisosteric modification of known bovine α-l -fucosidase inhibitors. Abstract : Bioisosteric modification of known fucosidase inhibitorsA andB, resulted in three new types of molecules, 4b, 5c and6a (belonging to furopyridinedione, thiohydantoin and hydantoin chemotypes) that could potentially bind to α-l -fucosidase (bovine kidney origin). Molecular docking revealed and compared the putative binding interaction between4b, 5c and6a withA andB against the active site of a homology model of α-l -fucosidase. Based on this initial investigation, design and synthesis of a library of small molecules based on furopyridinedione, thiohydantoin and hydantoin, followed by their in vitro screening against α-l -fucosidase (bovine kidney origin) generated a potent inhibitor (compound4e ) with IC50 of ∼0.7 μM. Compound4e possessed no cytotoxic properties when tested against healthy mammalian COS-1 cells. Reaction kinetics study suggested it to be a mixed inhibitor. Finally compounds4a, b, e andf, bearing the furopyridinedione motif also exhibited substantial inhibition of the proliferation of MCF 7 breast cancer cells.